MEMAHAMI REKONSTRUKSI KEBAHAGIAAN PADA ORANG DENGAN HIV/AIDS (ODHA) - Arriza, Beta Kurnia; Dewi, Endah Kumala; Kaloeti, Dian Veronika Sakti (Jurnal Psikologi, 2011)
This qualitative study aims to explore how the happiness reconstruction of the people living with HIV/AIDS. Data was collected by in-depth interview and narrative types observation into the three subject of this. People living with HIV/AIDS experienced a big life changes, including changes in health status, changes in emotional and their social. Given the complexity of this disease and its widespread effects on individuals’ lives, it might lead to significant psychological distress. When life is difficult, finding a way to be happy may be agreat challenge. That search for happiness may well involve rewriting goals and revisiting priorities. Findings indicated that to reconstruct their happiness, people living with HIV/AIDS experienced several things such as positive interpretation of their conditions and their lives; turning point; self-acceptance, also remeaning of the illness and happiness. Result showed that two of three subjects did the happiness reconstruction, nevertheless the other one did not do the happiness reconstruction because of the existence of negative interpretation of her illness and life. By happiness reconstruction they passed through, they feel happy with their lives, with their activity to be a caregiver and an activist. They have a high level of positive affect and a low level of negative affect. This study also revealed factor that contribute to happiness reconstruction, including maturity, personality, needs, family and social support, and religiousity.Keywords : happiness reconstruction, people living with HIV/AIDSPermalink : http://www.ejournal.undip.ac.id/index.php/psikologi/article/view/2889